STUDI EKSPERIMEN BETON TANPA PASIR DENGAN TIGA FAKTOR AIR SEMEN MENGGUNAKAN JENIS SEMEN PCC - ., Manah; Mungok, Chrisna Djaya; ., Herwani (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2014)
Hollow concrete is the concrete without sand to the constituent material consisting of coarse aggregate , cement and water .In this study, a coarse aggregate of crushed stone and cement Portland Cemen Composite (PCC) . In the manufacture of test specimens were used that method Modified ACI method then planned factor that varies the Water Cement 0.4 , 0.6 , and 0.8 . Specimens made ​​cylindrical with Æ 15 cm , and 30 cm high . Testing / testing only large compressive strength tested. From the results of the examination and calculation of compressive strength of concrete is affected by FAS 0.8 , 0.6 , and 0.4 . each produce characteristic concrete compressive strength of 5.419 MPa , 12,110 MPa , 29,303 MPa. Slump obtained using 3 variations of FAS are: 9 cm , 10 cm , and 10 cm . Average volume weight - average age of 28 days resulted in different variations - different , namely : 2,196,456 kg /m3; 2,286,325 kg /m3 , 2,379,965 kg / m3 . Price - the price the lower the FAS showed that the higher the compressive strength of concrete characteristics and the higher the volume gained weight Keywords: Concrete without sand, water cement factor (FAS) , compressive strength , Slump , Heavy volume